The Curious Incident of the Dog in the Night-time romanında ve Jack of the Red Hearts filminde hipersensitivite ve hiposensitivite sorunları - Tulgar, Alper (Yakup YILMAZ, 2022)
Janet Grillo tarafından yönetilen Jack of the Red Hearts filmi Taylor Richardson tarafından canlandırılan otistik genç kız Glory karakteri ve Glory’nin bakıcısı olarak eve alınmak için kimliğini gizleyen Jack (Jenny Jaffe) karakteri arasındaki güçlenen ilişkiyi inceler. Mark Haddon’ın The Curious Incident of the Dog in the Night-time adlı romanı otizm spektrumunda olan Christopher’ın aşırı duyarlılık tepkimelerini ve uyaranlara karşı verdiği tepkilerin azlığını yansıtır. Temsil açısından otistik karakterler filmlerde ve romanlarda özellikle artan ön yargılara maruz kalmaktadır. Bu ön yargılar Rain Man filmiyle başlamış ve tüm otistik bireylerin dâhi olduğu klişesini doğurmuştur. Böylesine kırılması güç bir klişeye sahip olan otistik bireyler için kendileri hakkında yapılan her film ve yazılan her roman sadece yönetmenin ve yazarların otizm hakkında kişisel görüşlerini ve sınırlı deneyimlerini yansıtabilecekleri ürünler olarak değerlendirilmemelidir. Otistik bireylerin toplumdaki algısını başta sinema ve edebiyat olmak üzere kurgusal ürünler şekillendirmektedir. Kurgu eserler ve otizm arasındaki bu mutlak bağın bilincinde olmak hem otistik bireylerin temsil sorununa çözümler getirecek hem de nörotipik ebeveynlerin ihtiyaçlarına cevap verecektir. Seçilen filmde otistik bireyin evlilikte sorunlara neden olduğunun gösterilmesi ve annenin “cure autism now” (otizmi şimdi tedavi et) kupasını kullanması otizmi bir sorun ve hastalık olarak yansıtır. Bununla birlikte bakıcı ve otistik genç kız arasında oluşan bağ ön yargıların yıkımına bir örnek oluşturur.

Directed by Janet Grillo, Jack of the Red Hearts examines the growing relationship between the autistic teenage girl Glory, played by Taylor Richardson, and Jack (Jenny Jaffe), who hides her identity to be taken into the house as Glory's babysitter. Mark Haddon’s novel The Curious Incident of the Dog in the Night-time reflects the hypersensitive reactions of Christopher, who is on autism spectrum and how he under responds to sensory stimuli. In terms of representation, autistic characters are especially exposed to increasing prejudices in films and novels. These prejudices started with the movie Rain Man and gave birth to the stereotype that all autistic individuals are geniuses. For autistic individuals, who have such a hard-to-break stereotype, every film made and every novel written about them should not be considered as products in which directors and writers can only reflect their personal views and limited experiences about autism. Fictional products, especially cinema and literature, shape the perception of autistic individuals in society. Being aware of this absolute link between fictional texts and autism will both provide solutions to the representation problem of autistic individuals and respond to the needs of neurotypical parents. In the selected movie, demonstrating that the autistic individual causes problems in marriage and the mother’s use of the “cure autism now” cup reflect autism as a problem and a disease. However, the bond formed between the caregiver and the autistic young girl is an example of the destruction of prejudices.
Issues of hyper- and hypo-sensitivity in the novel The Curious Incident of the Dog in the Night-time and the movie Jack of the Red Hearts
Keywords: Linguistics; Dilbilim; Literary Studies; Edebi Çalışmalar